Changes in Attachment to Place: Urban Transformation and Older People in İstanbul - Bay, Betul Duman; Senturk, Murat (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2024)
Although research on urban transformation is abundant, its relationships and effects on place attachment in informal areas of developing country contexts are rare. Our study focuses on the effects of these urban transformations, in situ and through relocation, on the physical and social dimensions of place attachment of older people in informal neighbourhoods of & Idot;stanbul, which has one of the highest populations of older people in Turkey. Following in-depth interviews with 30 older people, two primary categories were identified based on their orientation to the new neighbourhood: displaced and stayers. Members of a subcultural group and individuals with religious-conservative views have felt displaced and seek to recreate a similar sense of community and belonging either by returning to the old neighbourhood (returnees) or by moving to a similar sociocultural environment (movers), regardless of their experience of urban transformation with relocation and in situ. Stayers are of two types: those who are stuck in place, feel displaced and experience nostalgia for what was lost and those who have experienced positive changes in housing conditions, including improved comfort and security. These positive outcomes are mainly associated with the characteristics of the urban and political context of developing countries, including conditions such as informal settlement, economically driven urban transformation and the presence of family housing that compensates for community loss.
Keywords: Urban transformation; relocation; informal settlements; place attachment and older people; AGING IN-PLACE; RESIDENTIAL RELOCATION; DISPLACEMENT; NEIGHBORHOOD; REDEVELOPMENT; REGENERATION; PERSPECTIVE; ISTANBUL; Sociology